2014
DOI: 10.2298/vsp1412097b
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of local hemostatic modalities in anticoagulated patients undergoing tooth extractions

Abstract: In therapeutically anticoagulated patients tooth extractions can be safely performed without altering the dose of anticoagulant medication if efficient local hemostasis is provided. In most cases; in patients with INR ≤ 3.0 after extraction of one or two teeth postoperative bleeding can be controlled with local pressure, without any additional local hemostatic measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…However, some obstacles exist that limit the use of those agents, for example, the high cost of fibrin glue [15, 16] and the complex technique of tranexamic acid usage [25]. On the other hand, a Serbian study showed that local pressure is sufficient for adequate hemostasis in most cases of teeth extraction if INR is less than or equal to 3 [26]. It is noteworthy that suturing is not always necessary and should be reserved for instances where local hemostasis fails or when there is extensive tissue damage [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, some obstacles exist that limit the use of those agents, for example, the high cost of fibrin glue [15, 16] and the complex technique of tranexamic acid usage [25]. On the other hand, a Serbian study showed that local pressure is sufficient for adequate hemostasis in most cases of teeth extraction if INR is less than or equal to 3 [26]. It is noteworthy that suturing is not always necessary and should be reserved for instances where local hemostasis fails or when there is extensive tissue damage [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the beneficial effect of these local hemostatic agents in preventing bleeding in dental surgery, available data comparing their effectiveness and efficiency is still scarce and inconclusive. Methodological heterogeneities, such as the lack of a standard therapy and comparable treatment regimens, are noticeable among studies, as well as the reduced number of randomized controlled trials [2,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Effectiveness Of Different Biosurgical Hemostatic Agents In mentioning
confidence: 99%
“…The results of most studies show that dental extractions can be performed safely without discontinuing OAT if INR is within the therapeutic range (INR ≤ 4.0) and if appropriate local hemostatic measures are provided 14,[28][29][30][31][32][33][34][35][36][37][38] . The most commonly used local hemostatic agents and measures are: oxidized regenerated cellulose, absorbable gelatin or collagen sponges, fibrin glue, antifibrinolytics applied directly into the wound or in the form of a solution as a mouthwash and wound suturing [39][40][41] .…”
Section: Dental Treatment Of Patients Taking Oral Anticoagulant Drugsmentioning
confidence: 99%